The influence of sports on paralympic athletes’ personal development - Kokun, Oleg M.; Baranauskienė, Ingrida; Shamych, Oleksandr M. (Social Welfare: Interdisciplinary Approach, 2018)
One of the most effective ways of integrating people with disabilities into society and ensuring their comprehensive personal development is to engage people with disabilities into Paralympic Games. Such engagement creates the necessary conditions to socialize people with disabilities, to adapt their physical and mental states to existing living conditions, to ease negative manifestations of their psycho-emotional states, to promote their self-realization. The article presents the results of the research determining the impact of sports on Paralympic athletes’ personal development. The comparison of the indicators of psychological well-being and hardiness of Paralympic athletes with normative values, the indicators shown by students without disabilities and students with disabilities has confirmed proven clear positive influence of sports on Paralympic athletes’ personal development. In particular, Paralympic athletes achieve an optimal level of psychological well-being and a significant increase in all psychological hardiness components.
Keywords: Paralympic sports; people with disabilities; self-realization; psychological factors of sports achievements